A new species of Neoathripsodes Holzenthal, 1989 (Trichoptera: Leptoceridae) with new generic and species records in Bahia State, Brazil - Dias, Everton S.; Quinteiro, Fabio B.; Calor, Adolfo R. (Zootaxa, 2015)
Trichoptera is the most species-rich clade of exclusively aquatic insects. In Brazil, 645 species have been recorded, distributed in 70 genera and 16 families. In the Northeast Region of Brazil, 85 species have been recorded, including 56 in Bahia State. Sixteen of the Northeast Region species belong to the family Leptoceridae. Among these, the long-horned caddisfly genus Neoathripsodes Holzenthal has been a monotypic genus since its erection more than 26 years ago. It is an endemic genus in the states of Minas Gerais, Rio de Janeiro and São Paulo and only the male stage has been described for its only known species, Neoathripsodes anomalus. In this paper, we describe a new species of Neoathripsodes, with the first description of a female in this genus. Additionally, we present new records for the family Leptoceridae in Bahia, especially from the Serra Bonita Mountains, in order to help solve a long-term problem in Brazilian caddisfly research: An uneven proportion of studies in some regions of the country due to historical reasons. The Northeast Region of Brazil still remains a neglected area in which efforts to unearth its biodiversity should be focused. In this work, four species are recorded for the first time for Bahia State and its Serra Bonita Mountains: Grumichella rostrata Thienemann 1905, Neoathripsodes holzenthali n. sp., Nectopsyche fuscomaculata Flint 1983, and Notalina cipo Holzenthal 1986. Neoathripsodes and Notalina are new generic records for Bahia State. The following four species are new records for Serra Bonita: Atanatolica bonita Costa & Calor 2014, Oecetis martinae Quinteiro & Calor 2015, O. furcata Quinteiro & Calor 2015, and Triplectides gracilis (Burmeister 1839). Additional new distributional records for Bahia State are included in this study.